The Fund's Transparency Policy : Review of Experience and Next Steps. (Policy Papers; Policy Paper ;, 2002)
This paper reviews the experience with transparency of the Fund's activities and its members' policies. Transparency of the Fund as an institution has now become much more systematic. Fund missions consult more regularly with a broad group of interested parties. The Independent Evaluation Office has been established to provide objective and independent evaluation of issues related to the Fund. The Fund's transparency has also been increased through external consultations on, and independent evaluations of, its own policies and more systematic publication of policy papers. Finally, the Fund has enhanced the provision of information to the public through its website, and a substantial percentage of documents covering a wide range of topics is now published. Overall, activities of the Fund are now subject to much greater public scrutiny.